Intensity of Rice Field Land Utilization for Rice and Watermelon Crops (Case Study: Paya Itik Village, Galang District, Deli Serdang Regency) - Hutapea, Kenal P.; Sitorus, Ragnar Oktavianus; Purba, Trinitianti (Journal of Agriculture, 2024)
This study aims to (1) determine the intensity of rice field land use for rice and watermelon plants and (2) determine the income of farmers in rice and watermelon farming in Paya Itik Village, Galang District, Deli Serdang Regency. The population of this study consisted of farmers who planted rice and watermelon on one piece of land alternately in Paya Itik Village. The sample of this study was 50 rice and watermelon farmers alternately. Data collection used primary data methods with direct interviews with farmers to calculate the intensity of rice field land use for rice and watermelon plants. Data analysis used qualitative descriptive analysis. The results showed that the intensity of land for the first rice plant was 25%, watermelon was 8.33%, and the second rice was 25% with a land area of ??18.58 Ha. This is done because farmers use land to increase production during the planting season. The income of rice farmers in the first planting season was Rp. 5,819,699.444/year, watermelon plants Rp. The income obtained was 8,365,888.3/year, and in the second planting season of rice plants, it was Rp—6,293,452.46/year.